.DMF. I2 Complex as Efficient Green Catalyst in the Diels-Alder Reaction of Anthracene-9-Methanol With Maleimide. - GBAGUIDI, A. (My University, 2017)
Background: Interest for the Diels-Alder (DA) reaction has steadily increased over the time and the end of this remarkable development is not yet in sight. From its discovery on, the DA reaction has evolved through different stages of development, and since the beginning of the 21st century catalytic Diels-Alder reactions remains obviously one of the main areas of research. Methods: As there are striking similarities in the catalysis of both DA and Friedel-Crafts reaction, we therefore anticipated that DMF (a weak Lewis base) and iodine (a weak Lewis acid) could act synergistically and smoothly in the DA reaction, and we selected the cyclo-addition of maleimide to anthracene- 9-methanol as our benchmark reaction in order to be able to accurately compare our actual data with the results of our previous publications. Results: Based on Pearson's SHAB (Soft and Hard Acids and Bases) theory, we have first established that the Diels-Alder cyclo-addition of our benchmark reaction (anthracene-9-methanol and maleimide) is a process submitted to generalized acid-base catalysis and in a second step we have developed within the context of the Green Chemistry an original efficient catalyst i.e. the DMF.I2 complex where DMF acts as Lewis base and iodine as Lewis acid. In order to expand the scope of title catalyst, the cyclo-addition of tetracyclone with N-phenylmaleimide was carried out successfully using DMF.I2 in n-butanol and led to both endo and exo adducts in good yields. Conclusion: It is noteworthy that the molar ratio of diiodine vs. dienophile can be successfully scaled down to 10% without significant detrimental effect on the time of reaction and final yield (1 h, 100°C, 93%).
Keywords: Diels-alder reaction; maleimide - N; N-dimethylformamide.iodine complex; green chemistry; DMF. I2 complex; green catalysts; tetracyclone.